On the number of stable positive solutions of weakly nonlinear elliptic equations when the diffusion is small - Dancer, Edward N. (Topological Methods in Nonlinear Analysis, 2021)
We study the exact number of stable positive solutions of weakly nonlinear elliptic equations with small diffusion under rather general conditions on the nonlinearity.